2015
DOI: 10.1007/s12031-015-0583-9
|View full text |Cite
|
Sign up to set email alerts
|

ALFF Value in Right Parahippocampal Gyrus Acts as a Potential Marker Monitoring Amyotrophic Lateral Sclerosis Progression: a Neuropsychological, Voxel-Based Morphometry, and Resting-State Functional MRI Study

Abstract: The aim of this study is to analyze cognitive impairment in amyotrophic lateral sclerosis (ALS). Forty-four participants matched for age, sex, and educational background were enrolled as the sporadic ALS group (n = 22) and the control group (n = 22). All participants completed comprehensive neuropsychological tests, including the Mini-Mental State Examination (MMSE), the Montreal Cognitive Assessment (MoCA), the Stroop Color-Word Interference Test (SCWT), the Wisconsin Card Sorting Test (WCST), and the Frontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“… Zhu et al (2015) found increased ALFF in patients of ALS compared to healthy controls in the right parahippocampus, left inferior temporal gyrus, left anterior cingulate, right superior frontal gyrus and left middle occipital gyrus. Increased ALFF was further reported to be found in the right inferior frontal gyrus and left middle frontal gyrus, and decreased ALFF right postcentral gyrus and bilateral fusiform and inferior occipital gyri ( Luo et al, 2012 ).…”
Section: Evidence On Resting-state Fmri In Neurodegenerative Diseasesmentioning
confidence: 78%
“… Zhu et al (2015) found increased ALFF in patients of ALS compared to healthy controls in the right parahippocampus, left inferior temporal gyrus, left anterior cingulate, right superior frontal gyrus and left middle occipital gyrus. Increased ALFF was further reported to be found in the right inferior frontal gyrus and left middle frontal gyrus, and decreased ALFF right postcentral gyrus and bilateral fusiform and inferior occipital gyri ( Luo et al, 2012 ).…”
Section: Evidence On Resting-state Fmri In Neurodegenerative Diseasesmentioning
confidence: 78%
“…A flow diagram showing the identification and exclusion of studies is provided in Figure 1. Ultimately, a total of 37 studies were included in the meta-analysis, including 19 on bvFTD (one study included three bvFTD groups) (Rosen et al, 2002;Grossman et al, 2004;Boccardi et al, 2005;Kanda et al, 2008;Seeley et al, 2008;Ash et al, 2009;Kipps et al, 2009;Libon et al, 2009;Pardini et al, 2009;Hornberger et al, 2011;Farb et al, 2013;Massimo et al, 2013;Lagarde et al, 2015;Yokoyama et al, 2015;Dermody et al, 2016;Mandelli et al, 2016;Melloni et al, 2016;Buhour et al, 2017a;Bertoux et al, 2018) and 18 on ALS (Chang et al, 2005;Grosskreutz et al, 2006;Agosta et al, 2007;Mezzapesa et al, 2007;Thivard et al, 2007;Grossman et al, 2008;Cosottini et al, 2012;Tedeschi et al, 2012;Meoded et al, 2013;Cerami et al, 2014;Zhang et al, 2014;Devine et al, 2015;Raaphorst et al, 2015;Tavazzi et al, 2015;Zhu et al, 2015;Buhour et al, 2017b;Kim et al, 2017;Christidi et al, 2018…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…On the one hand, that this increased functional connectivity represents the compensation for structural damage ( Agosta et al, 2011 ), being exhausted when the burden of pathology increases. On the other hand, that it represents the reduced local inhibitory function ( Turner and Kiernan, 2012 ), which characterizes the early disease, as supported by the MRS GABA concentrations decrease in the primary motor cortex ( Foerster et al, 2013a ) and decreased uptake of 11 C-flumazenil in the primary motor cortex and frontal cortex by means of PET ( Zhu et al, 2015 ).…”
Section: Quantitative Brain Mr Imaging Biomarkers In Alsmentioning
confidence: 99%
“…Finally, the connectivity between the left sensorimotor cortex, right parahippocampal gyri and fourth cerebellar lobule have been correlated with disease severity ( Agosta et al, 2011 ). The activity in the right parahippocampal gyri and connectivity in the frontal cortex have been correlated with disease progression and duration ( Luo et al, 2012 ; Zhu et al, 2015 ), while activity in the left anterior cingulate and left temporal gyrus has been correlated with cognitive parameters ( Zhu et al, 2015 ). The changes in the hippocampal region, including its connectivity, are related to its dysfunction; and the dysfunction contributes to the clinical heterogeneity of ALS ( Christidi et al, 2018 ).…”
Section: Quantitative Brain Mr Imaging Biomarkers In Alsmentioning
confidence: 99%